The Finnish corporate network – empirical findings from the board room network - Pihlava Matti (Aboa Centre for Economics (ACE), 2016)
This paper studies Finnish firms and especially it's boardroom network and the effects that it has on financial actions. Compared with earlier studies, this study also takes into consideration both firms that are not connected and uses them as a natural comparison, as well as principal component membership as a relevant network centrality measure. Based on the firms' year end reports from 2009 to 2013, the results show that firms that are connected are on average greater in size, invest more but their Return On Investments are lower. Higher network centrality further increases the effects. With firm-specific controls and yearly fixed effects the results seem robust. The magnitude of the results can be ambiguous due to simultaneous endogeneity between the variables. Compared to previous studies, the results are contrary to what has been noted earlier. Seasonal changes or general economic outcomes might explain these results.
Keywords: D85; L14; G34; 330; Network Analysis; Networks; Corporate Governance